Impact of Microcredit on the Performance of Micro and Small Enterprises (MSEs) in Yemen: With the Mediating Role of the Beneficiaries’ Satisfaction - Ahmed AL-Maamari, Osamah; P, Vedava; Alrefaei, Noufal (Jordan Journal of Business Administration, 2025)
This study examined the impact of microcredit on the performance of Micro and Small Enterprises (MSEs) in Yemen, with the mediating role of the beneficiaries’ satisfaction. To accomplish the goal of this study, descriptive and analytical research methods are adopted. The study focused on the owners of MSEs in Yemen who have access to microcredit. The total number of active clients who get credit from MFIs was 90,946 active clients, and the sample size was 398. Data was examined by using SPSS to provide quantitative descriptive statistics measures, and to evaluate the theoretical model of this study. PLS-SEM route modeling was utilized using Smart PLS 3.2.9 software, because it replicates the standard regression approach. PLS path modeling was judged the most acceptable technique in this study. Further, the results show that microcredit has a significant impact on profitability, sales growth, and employment growth, while it has no significant impact on the increase in assets. Beneficiaries’ satisfaction mediates the relationship only with profitability, sales growth, and increase in assets, while having no significant impact on employment growth.